Mechanisms for improving service based on the system of digitalization of emergency medical care - Gafurov Abduvoitjon Khuseynovich (THE INNOVATION ECONOMY, 2026)
This article covers the issues of improving services based on the automation system of emergency medical services. Through this system, the creation of a radio communication network in the Emergency Medical Service, the introduction of an electronic automated management system for emergency medical assistance, the establishment of a single call center - “Call-centers” for each region, and all regional It is aimed at receiving calls only through these “Call-centers”, providing for monitoring the movement of emergency medical vehicles online, installing GPS trackers and radio communication devices, and establishing an electronic automated management system for emergency medical care.